2020
DOI: 10.7717/peerj.9488
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of potato peel and agro-forestry biochars supplementation on in vitro ruminal fermentation

Abstract: Background The awareness of environmental and socio-economic impacts caused by greenhouse gas emissions from the livestock sector leverages the adoption of strategies to counteract it. Feed supplements can play an important role in the reduction of the main greenhouse gas produced by ruminants—methane (CH4). In this context, this study aims to assess the effect of two biochar sources and inclusion levels on rumen fermentation parameters in vitro. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In vitro rumen batch culture is a technique widely used for predicting the degradability and nutritive value of feed sources ( 23 , 24 ). It is also used to screen the potential of non-conventional additives and feeds, such as biochars, microalgae, and seaweeds ( 6 , 25 , 26 ), to modulate ruminal fermentation and, in particular, to reduce methane production. Despite its simplicity and the possibility of testing multiple samples at a single batch under similar conditions and without interference from the metabolic process of the host, several factors may influence the consistency of results ( 11 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro rumen batch culture is a technique widely used for predicting the degradability and nutritive value of feed sources ( 23 , 24 ). It is also used to screen the potential of non-conventional additives and feeds, such as biochars, microalgae, and seaweeds ( 6 , 25 , 26 ), to modulate ruminal fermentation and, in particular, to reduce methane production. Despite its simplicity and the possibility of testing multiple samples at a single batch under similar conditions and without interference from the metabolic process of the host, several factors may influence the consistency of results ( 11 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ash content that results from the decomposition of the inorganic matter of biomass [23] is expected to be low in wood-based biomass when compared to mineral-rich biomass, such as grass, manure, litter, and solid waste [36]. Wood, bamboo, corncob, corn stover, pellets (miscanthus, softwood, wheat straw, and oilseed rape straw), rice straw, and potato peel biochar reported less than 25% of ash content, while rice husk presented higher than 40% [37][38][39][40][41][42][43][44]. The ash content has been demonstrated to be relevant for the surface polarity and distribution of pores, thus influencing the sorption capacity of the material.…”
Section: The Role Of Biomass and Production Conditions On Biochar Cha...mentioning
confidence: 99%
“…A comparison between studies is further complicated by the diversity of biomass sources used (e.g., rice husk, pine wood, corn stover, cashew nutshell, tree pruning, rice straw, corncob, bamboo) that might affect VFA profile, thus introducing a confounding effect on the mechanism of CH 4 reduction. Most studies that compared the impact of biomass sources on enteric CH 4 production [37,38,41,42] observed no differences among biochar sources. Conversely, Van Dung et al [44] found rice straw and bamboo biomass to reduce CH 4 production compared to corncob, at 4 and 48 h of incubation, but not at 24 h. Moreover, these authors observed an interaction effect between biomass source and pyrolysis temperature [44], supporting the need for a multi-aspect analysis of biochar's chemical and physical properties.…”
Section: In Vitro Short-term Studiesmentioning
confidence: 99%
See 2 more Smart Citations